Health Education Concerning Stroke Patients Treatment on Family's Readiness to Go Home for Non-Hemorragic Stroke Patients - Handayani, Sri; Hafidudin, Muhammad; Wulandari, Astrie (Green Publisher Indonesia, 2024)
Stroke has physical and mental impacts so that stroke clients depend on their families and need long-term care and recovery. Therefore, family readiness is needed in caring for stroke patients. Through health education using leaflets, we try to help patient family members be ready to care for stroke patients while at home. The research aims to determine the effect of health education on the readiness to return home to families of non-hemorrhagic stroke patients in the Inpatient Room at RSU PKU Muhammadiyah Delanggu. The research used a pre-experimental design method type one group pretest-posttest. The sample was taken by purposive sampling and obtained 32 respondents using the Slovin formula. The instrument uses leaflets and questionnaires. The data analysis technique uses a paired t test. It was found that the majority of families of stroke patients were female (65,6%), aged 46-55 years (37.5%), had a high school education (53.1%), did not work or were housewives (53,1% ), and the family caring for the child (62.5%), before being given health education using leaflets related to the care of non-hemorrhagic post-stroke patients, the majority of family members were less prepared (62.5%) and after being given health education, the majority of family members feel ready (87,5%). There is an influence of health education regarding the care of stroke patients on the readiness to return home to the families of non-hemorrhagic stroke patients in the Inpatient Room at RSU PKU Muhammadiyah Delanggu (p value 0.000 < 0,05).